ANALISIS TINGKAT KESEHATAN BANK PADA BANK PEMBANGUNAN DAERAH KALIMANTAN TIMUR - ., Marfu'ah (EKONOMIA, 2012)
This research a purpose to achive the description that is more clear abouth healty, fair healty, less healty, and unhealthy. There search was done at Bank Pembangunan Daerah Kalimantan Timur. The data which is used, are Balace Sheet statemen ,  income statement, the quality of productive asset statement, the calculation of provisions minimum capitalstatement and commitment and contingency statement.The implementation system of the soundness assement was based  Indonesia Bank Circular Letter, of No. 6 /10/PBI/2004 used CAMEL method, CAMEL is soundness bank assestment based on five factors , there are Capital,Asset Quality, Management, Earning and Liquidity.From the analysis was know that the financial statement of Bank Pembangunan Daerah Kalimantan Timur in 2011 was classified healty review from Capital, Assets Quality, Management, Earning and Liquidity. Based on the result calculation of Capital Adequacy Ratio in 2011 was 18,45% and quantification of assessment was 185,5 with credit factor value after weigting was 25 so as to be categorized healty. Ratio of Produktive assets Clasifeied (APYD) against the Produktive assets (AP) in 2011 was 3,06 % and quantification of this assessment was 82,93 with credit factor value after weigthing was 20,73 so as to be categorized healty. Ratio Net Profit Margin in 2011 25,43 % this was showed more effective in generating nett income and showed the better perfomance that can be categorized healty. ROA (Retrn On Assets) ratio in 2011 was 3,70 % and quantification assessment was 247,66 with credit factor value after weighting factor was 5 so as to be categorized healty.Operational cost to Operational Income (BOPO) in 2011 was 63,86% and quantification of this assessment was 451,75 with credit factor of weigthing factor was 5 so as to be categorized healty. Loan To Debt ratio (LDR) in 2011was 59,95% and quantification assessment was 224,20 with credit factor value after weigthing factor was 10 so as tobe categorized healty.  The result of conclusions from this research was accepted because Bank Pembangunan daerah Kalimantan Timur  in 2011 has a healty predicate.